Community-based waste segregation as a foundation for coastal resilience: an environmental politics perspective - Yanti Hastuti (Journal of Character and Environment, 2026)
Background: Indonesia's coastal communities face increasing environmental pressures from climate change and ineffective waste management, threatening ecosystem sustainability and community resilience. Although community-based waste segregation has been widely promoted, existing studies provide limited understanding of its governance dimensions and contribution to coastal resilience. Therefore, this study systematically reviews the literature to identify governance patterns and research gaps related to community-based waste segregation for coastal resilience. Methods: This study employed a Systematic Literature Review (SLR) using a qualitative synthesis approach. Data were sourced from peer-reviewed journals indexed in Scopus, Web of Science, Google Scholar via SciSpace, and other additional source. Six eligible studies were selected and comparatively analyzed to examine governance patterns supporting community-based waste segregation and coastal resilience. Findings: Six eligible studies were reviewed. The findings indicate that community-based waste segregation is more effective when supported by polycentric governance involving communities, governments, and other stakeholders. Adaptive governance was reflected in collaborative decision-making, institutional flexibility, and cross-scale coordination, whereas limited institutional support reduced the long-term sustainability of waste management initiatives. Conclusion: Community-based waste segregation contributes to the socio-ecological resilience of coastal areas by strengthening sustainable collaborative governance. Its effectiveness depends on institutional support, cross-scale coordination, and inclusive environmental policies. Strengthening polycentric governance is therefore essential for the sustainability of community-based waste segregation. Novelty/Originality of this article: This study synthesizes existing evidence to explain how polycentric governance and institutional arrangements shape the contribution of community-based waste segregation to coastal resilience, providing an integrated governance perspective that has received limited attention in previous studies.